Mario's Pizza Palace a manual accounting practice set - Pabst, W.; Perrin, Brian (John Wiley & Sons, 2015)
Mario's Pizza Palace is a manual accounting practice set for a small company. This practice set provides experience in manually recording and posting a variety of business transactions common to small businesses, so that students gain an understanding of the flow of data in an accounting system. Many of these processes occur out of sight in a computerised accounting system. Completion of the practice set for a one-month period should ensure a greater appreciation of; the steps in the accounting cycle for a small business, the use of special journals for processing data more efficently, the use of subsidiary ledgers to remove detail from the general ledger, the perpetual inventory system, the bank account reconciliation, balance-day adjustments and the general ledger closing process, how the accounting cycle culminates in the preparation of financial statements and how the goods and services tax (GST) impacts on accounting.